The paradox of human resource investment in smoking households - Oktavianti, Henny; Burhan, Umar; Ekawati, Marlina; Badriyah, Nurul (Asian Development Policy Review, 2023)
This research aims to analyze the effects of cigarette expenditure on human resource investment in smoking households. Independent variables used besides cigarette expenditure were income and the level of education of the head of the family. The control variables used were poverty, residence location, the number of working family members, and the number of family members. The method of data analysis used in this study was Simultaneous Equation Estimation. This method was used due to the interplay between dependent and independent variables. The parameter estimation process in a simultaneous equation model employs the two-stage least squares (2SLS) method due to model identification indicating over-identification. The observed analytical units are two-generation smoking households, making the observations in this research intergenerational in character. The results of the study indicate that cigarette expenditures will reduce human resource investment in smoker households in the long term. A bigger impact was apparently found when the condition occurred in poor families. Poor smoking households will be trapped in a vicious cycle of poverty that is worsened by the addictive trait of cigarettes, which will reduce other essential expenditures in the household (such as education and health). The situation of poor smoking households will also infect the next generation (children’s households), where intergenerational influences have taken place. A situation where cigarettes become an expenditure that cannot be displaced but rather will displace expenditures for education and health investment.